Role of microbial laccases in valorization of lignocellulosic biomass to bioethanol - Haq, Ikram ul; Saleem, Aroona; Chaudhary, Rida; Alessa, Abdulrahman H.; Nawaz, Ali; Du, Chenyu (Frontiers in Bioengineering and Biotechnology, 2024)
The persistent expansion in world energy and synthetic compounds requires the improvement of renewable alternatives in contrast to non-sustainable energy wellsprings. Lignocellulose is an encouraging feedstock to be utilized in biorefineries for its conversion into value-added products, including biomaterials, biofuels and several bio-based synthetic compounds. Aside from all categories, biofuel, particularly bioethanol is the most substantial fuel derived from lignocellulosic biomass and can be obtained through microbial fermentation. Generally, extreme settings are required for lignocellulosic pretreatment which results in the formation of inhibitors during biomassdegradation. Occasionally, lignin polymers also act as inhibitors and are left untreated during the pretreatment, engendering inefficient hydrolysis. The valorization of lignocellulosic biomass by laccases can be viewed as a fundamental trend for improving bioethanol production. However, one of the main obstacles for developing commercially viable biofuel industries is the cost of enzymes, which can be resolved by utilizing laccases derived from microbial sources. Microbial laccases have been considered an exceptionally integral asset for delignification and detoxification of pretreated LCB, which amplify the resultant fermentation and saccharification processes. This review provides a summary of microbial laccases and their role in valorizing LCB to bioethanol, compelling enthralling applications in bio-refining industries all across the globe.